Solution structure of the integral human membrane protein VDAC-1 in detergent micelles - Hiller, Sebastian (2008)
The voltage-dependent anion channel (VDAC) mediates trafficking of small molecules and ions across the eukaryotic outer mitochondrial membrane. VDAC also interacts with anti-apoptotic proteins from the Bcl-2 family and this interaction inhibits release of apoptogenic proteins from the mitochondrion. We present the NMR solution structure of recombinant human VDAC-1 reconstituted in detergent micelles. It forms a 19-stranded β-barrel with the first and last strand parallel. The hydrophobic outside perimeter of the barrel is covered by detergent molecules in a belt-like fashion. In the presence of cholesterol recombinant VDAC-1 can form voltage-gated channels in phospholipid bilayers similar to the native protein. NMR measurements revealed the binding sites of VDAC-1 for the Bcl-2 protein Bcl-x(L), for β-NADH and for cholesterol. Bcl-x(L) interacts with the VDAC barrel laterally at strands 17 and 18.